A Catalogue of New Varieties - Taylor, Lloyd W. H.; Kodysz, Michael; Bianchini, Davide (KOINON: The International Journal of Classical Numismatic Studies, 2021)
1. Seleukid Kingdom, Seleukos I Nikator, 312-281 BC, Babylonia Uncertain Mint 6A (Opis). 2. Uncertain Eastern Seleukid Satrapy, c. 300-250 BC. 3. Uncertain East, Sogdiana (?), c. 240-200 BC. 4. Uncertain East, Sogdiana (?), c. 240-200 BC. 5. Septimius Severus, Emesa 6. Septimius Severus, Emesa 7. Septimius Severus, Emesa 8. Julia Domna, Emesa 9. Elagabalus, Rome 10. Elagabalus, Rome 11. Elagabalus, Eastern (usually attributed to Antioch) 12. Severus Alexander, Eastern (usually attributed to Antioch) 13. Volusian as Augustus, Antioch mint. 14. Claudius II, Siscia mint. 15. Claudius II, Antioch mint.